AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BAWANG MERAH (Allium cepa L.) TERHADAP BAKTERI Staphylococcus aureus - Misna Misna; Khusnul Diana (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2016)
One of the plants tat used in medicine is garlic (Allium cepa L.). In addition as medicinal traditional plant, garlic is used as food spice. Garlic utillizated for the root only, and the skin which is rich with fibrous and flavonoid is wasted. This research aim is to know if the garlic skin have antibacterial activity against Staphylococcus aureus. Garlic skin made into extract with maseration methode using 96% ethanol. Antibacterial activity test with hollow diffusion methode. Te parameter used are inhibition zone created. Variation of concentration are 5%b/v, 10%b/v, 20%b/v, 40%b/v, 60%b/v, 80%b/v. Activity test made with extract added in the hole in the Staphylococcus aureus media, then incubated at temperature 370C 24 hours. The inhibition zone 5%, 10%, 20%, 40%, 60%, and 80% extract respectively were 7,00mm, 8,30mm, 9,60mm, 11,00mm, 12,33m and 14,33mm